Applications of MDMA in Modern Medicine - A Literature Review - Wiktoria Podlasiewicz; Paweł Siudziński; Mateusz Łyko; Alicja Skoczylas; Jakub Kurasz; Wojciech Maj; Wiktoria Tomaszewska; Katarzyna Pala; Piotr Dudziak; Anna Nowak; Maria Golińska (Journal of Education, Health and Sport)
MDMA or 3,4- methylenedioxymethamphetamine is a psychoactive substance, exhibiting mild hallucinogenic properties, that became widely known as a recreational party drug. However, its ability in helping individuals access deeply rooted emotions has prompted significant interest in its potential applications within clinical practice. MDMA’s mechanism of action involves increasing the release of serotonin, dopamine and oxytocin. This process enhances neuroplasticity, fosters empathy and aids in trauma processing and fear extinction. This study aims to explore the potential uses of MDMA in medicine, particularly in treating mental illnesses. The article was developed using data from the „PubMed” and „Google Scholar” databases, with particular emphasis on articles published after 2021. When combined with psychotherapy, MDMA offers significant therapeutic benefits, especially for patients resistant to conventional treatments. Existing research primarily highlights its effectiveness in managing post traumatic stress disorder (PTSD) and anxiety disorders, with emerging evidence suggesting potential benefits for conditions like depression and eating disorder. While recreational use of MDMA poses risks, its use in a controlled environment demonstrates a favourable safety profile. Despite the highly promising results of MDMA- assisted therapy so far, additional clinical research is crucial to enable this drug to revolutionise future treatment methods.